Interventions for peri‐implantitis and their effects on further bone loss: A retrospective analysis of a registry‐based cohort. (18th June 2019) - Karlsson, Karolina; Derks, Jan; Håkansson, Jan; Wennström, Jan L.; Petzold, Max; Berglundh, Tord
Abstract: Objective: The aim of the present study was to assess interventions and their consequences with regard to further bone loss at sites diagnosed with peri‐implantitis. Materials and Methods: In 2017, records of 70 patients diagnosed with moderate/severe peri‐implantitis at ≥1 implant sites 4 years earlier were obtained. Changes of marginal bone levels during the study period assessed on radiographs and predictors of disease progression were identified by Cox regression and mixed linear modelling. Patient files were analysed for professional interventions related to the treatment of peri‐implantitis. Results: Mean bone loss (± SD ) at implants diagnosed with moderate/severe peri‐implantitis was 1.1 ± 2.0 mm over the observation period of 3.3 years. While non‐surgical measures including submucosal and/or supra‐mucosal cleaning of implants were provided to almost all patients, surgical treatment of peri‐implantitis was limited to a subgroup (17 subjects). Surgically treated implant sites demonstrated a mean bone loss of 1.4 ± 2.4 mm prior to surgical intervention, while only minor changes (0.2 ± 1.0 mm) occurred after therapy. Clinical parameters (bleeding/suppuration on probing and probing depth) assessed at diagnosis were statistically significant predictors of disease progression. Conclusions: Non‐surgical procedures were insufficient to prevent further bone loss at implant sites affected by moderate/severe peri‐implantitis. Surgical treatment of peri‐implantitis markedly diminished the progression of bone loss. Clinical assessments of bleeding on probing and probing depth at diagnosis predicted further bone loss.